IPV4/IPV6 security and threat comparisons - BULDU, ALİ (ELSEVIER SCIENCE BV, 2010)
Internet using is increasing rapidly. Internet occured as a result of commincating nodes with each. New internet users are joining to this structure and development of it is going on. In such a big structure, communication of two nodes is possible only if they find each other. Various addressing protocols have been developed to obtain this. The well-known is called Internet Protocol ( IP ). Currently IP is used IP Version 4 ( Ipv4). Ipv4 has limited address. This limited addresses does not meet the growth of internet. Because of inadequate internet address, IP Version 6 ( IPV6 ) was developed in 1995. Ipv6 brings many enhancement. Ipv6 was designed with security in mind. It is bringing security enhancments into modern IP network. This paper analyses Ipv6 and Ipv4 Threat Comparisons on two stage. First part focuses on the attacks with Ipv4 and Ipv6 similarities. Second part is focuses on the attacks with new considirations in Ipv6. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: IPv6; IPv4; IP security; Ipv6 security performance; IP threats; IP attacks; security comparision